O papel das interações professora-criança na concepção das professoras de creche - Silva, Patrícia Targino da (2015)
This study attempts to understand the role of teacher-child interactions in Early Childhood Education from the perspective of daycare teachers. This paper is anchored in the sociointeractionist theory represented by Vygotsky who states that human development occurs in a process mediated by the culture and the other people in interaction of the individual with the environment. The aim is to investigate the teachers’ conceptions on the role of teacher-child interactions in Early Childhood Education. The methodology had a qualitative approach in which we chose the multiple cases study. To meet the specific purposes we used the semi-structured interview as data seizure technique. The tools used to record were: notebook, microphone and camera. The field research was carried out in three Early Childhood Education Centers which criteria were to be part of the municipal school system in Fortaleza and meet daycare aged children. The subjects of the research were three teachers appointed by the coordinators for holding a work of excellence in the institutions and for being gazetted teachers. Data presentation and analysis were performed from three macro categories inspired in the specific purposes: childteacher interaction, child-child interaction; interaction in learning and development, and space and available materials. Analyzes suggest that the understanding of the teachers on the concept of child, childhood and Early Childhood Education defines the pedagogical practice. As there is the knowledge of the teachers about the current demands from daycare institutions we realized that they are reflecting on their practice and looking for ways to work out the theory. By speech they seem to understand that interactions are present in all situations and daycare environments and are fundamental to children learning and development.